Auto irrigate - The continuous irrigant delivery and intracanal aspiration system - Ridyumna Garain; Veena S Pai; G R Krishnakumar; M Bharathi; B Vedavathi; Jibin Karim (Wolters Kluwer Medknow Publications, 2022)
Aims: To compare the delivery of irrigant to the apical third of the root canals using an ingeniously designed continuous irrigation and intracanal aspiration system to standard irrigation techniques. Methods: Sixty-six freshly extracted single-rooted mandibular second premolars of similar dimensions with a single straight canal, confirmed radiographically, were selected and divided into three groups (n = 22) based on irrigation techniques employed: (i) manual dynamic activation, (ii) passive ultrasonic activation, and (iii) the system designed by the authors. Standard oval-shaped access cavities were prepared and the working length was determined radiographically. Instrumentation with ProTaper F2 rotary files was followed by irrigation with 2.5% NaOCl and saline using a 2.5 ml syringe and needle for Groups 1 and 2, and the irrigant delivery system for Group 3. A prefinal rinse with EDTA and a final rinse with saline was also carried out. Apical delivery of irrigant was evaluated by flooding the root canals with 1% toluidine blue dye for 30 seconds. The specimens were decoronated and split vertically and labiolingually and visualized under a stereomicroscope (×5 magnification) and photographed. The images were analyzed using ImageJ software to measure the unstained apical region. One-way ANOVA with Tukey's post hoc test was used to statistically analyze the results (P < 0.05). Results: The ingeniously devised irrigation delivery and intracanal aspiration system showed a significantly higher apical delivery of irrigant as compared to the other methods studied (P < 0.001). Conclusions: The proposed simple root canal irrigating device can be made with materials readily available. Comparing the same to standard techniques showed better irrigant delivery to the apical region. With further studies planned to evaluate smear layer removal and canal disinfection, we hope that this can serve as an efficient, cost-effective novel device that can be easily incorporated into clinical practice.